2007
DOI: 10.1364/oe.15.006218
|View full text |Cite
|
Sign up to set email alerts
|

Beam homogenizers based on chirped microlens arrays

Abstract: Lens array arrangements are commonly used for the homogenization of highly coherent laser beams. These fly's eye condenser configurations can be used to shape almost arbitrary input intensity distributions into a top hat. Due to the periodic structure of regular arrays the output intensity distribution is modulated by equidistant sharp intensity peaks which are disturbing the homogeneity. As a new approach we apply chirped microlens arrays to the beam shaping system. These are non-regular arrays consisting of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 7 publications
1
24
0
Order By: Relevance
“…The goniophotometer measurements with a monomode laser source showed that the linear diffuser generate a non periodic far field intensity distribution that was also observed by Wippermann et al [6] for chirped fly's eye condenser based beam homogenizers.…”
Section: Inspection and Characterizationsupporting
confidence: 74%
“…The goniophotometer measurements with a monomode laser source showed that the linear diffuser generate a non periodic far field intensity distribution that was also observed by Wippermann et al [6] for chirped fly's eye condenser based beam homogenizers.…”
Section: Inspection and Characterizationsupporting
confidence: 74%
“…In other words: every lenslet on the wafer can be designed to have its own position, orientation, size (mask #1), and focal length (mask #2). We used this enhanced design freedom in the randomization of arrays for homogenization [17], the channel-wise aberration correction of multichannel imaging optics [18] or simply the lateral arrangement of elements with different parameters on the same wafer [19]. A means to simulate -generalized‖ chirped or stochastic lens arrays in the ray tracing design and routines to calculate the corresponding mask data for each lenslet were implemented in our fabrication process [20].…”
Section: Mastering By Photolithographymentioning
confidence: 99%
“…These peaks can only be avoided if the illumination is partly coherent or if the periodicity is avoided. Wippermann et al [10] described a solution for avoiding the periodic structure with the help of a so called chirped microlens array. Another way to temporally smooth the spiked profile is to use rotating random diffusers.…”
Section: Diffraction and Grating Effectsmentioning
confidence: 99%